Features of Epstein–Barr Virus and Cytomegalovirus Reactivation in Acute Leukemia Patients After Haplo-HCT With Myeloablative ATG-Containing Conditioning Regimen - Ru, Yuhua; Zhu, Jinjin; Song, Tiemei; Ding, Yiyang; Zhu, Ziling; Fan, Yi; Xu, Yang; Sun, Aining; Qiu, Huiying; Jin, Zhengming; Tang, Xiaowen; Han, Yue; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Haploidentical donor hematopoietic cell transplantation (haplo-HCT) has become a preferred option for patients without HLA-matched donors, but it increases the risk of viral reactivations. Epstein-Barr virus (EBV) and cytomegalovirus (CMV) are common viruses post-HCT, but limited data have been reported in the setting of haplo-HCT. Methods: We conducted a retrospective study enrolled acute leukemia patients who received haplo-HCT with myeloablative conditioning regimen employing ATG in our center from July 2014 to July 2017. Results: Totally 602 patients were recruited including 331 with acute myeloid leukemia (AML) and 271 with acute lymphoblastic leukemia (ALL). One-year cumulative incidences of EBV (22.9% ± 2.4% vs 27.4% ± 2.8%, P = 0.169) and CMV (24.7% ± 2.4% vs 29.4% ± 2.8%, P = 0.190) reactivation were comparable between AML and ALL. EBV and CMV were independent risk factors for each other. In AML group, male recipients (HR = 1.275, 95%CI [1.001 – 1.624], P = 0.049) was an independent risk factor for EBV reactivation, and acute graft-versus-host disease (HR = 1.592, 95%CI [1.001 – 2.533], P = 0.049) for CMV reactivation. CMV rather than EBV reactivation was related to a trend of worsened treatment-related mortality (TRM) (15.6% ± 0.1% vs 10.2% ± 0.0%, P=0.067) and progression-free survival (PFS) (60.6% ± 4.1% vs 70.3% ± 2.3%, P=0.073), but significant impacts were revealed only in subgroup analysis. CMV reactivation resulted in a remarkable inferior 2-year overall survival (OS) (64.2% ± 5.7% vs 77.6% ± 3.2%, P=0.038) and PFS (55.0% ± 5.9% vs 71.9% ± 3.4%, P=0.042) in ALL patients. While in the subgroup EBV+/CMV-, relapse was lower in ALL patients (8.2% ± 0.2% vs 32.4% ± 0.8%, P = 0.010) compared to AML patients, which led to a superior 2-year OS (82.0% ± 6.2% vs 60.3% ± 8.8%, P = 0.016) and PFS (74.5% ± 7.0% vs 57.5% ± 8.4%, P = 0.036). Conclusion: We concluded that EBV and CMV reactivation were frequent in acute leukemia patients after haplo-HCT, with possibly distinctive risk factors from HLA-matched HCT. There could be a potential interaction between EBV and CMV, but impacts on transplant outcomes remained complex.